New metrics for assessing the performance of multi-microgrid systems in stand-alone mode. (June 2018) - Wang, Shouxiang; Zhang, Xingyou; Wu, Lei; Sun, Shumin
Highlights: A set of new metrics for quantitatively assessing the performance of multi-microgrid systems are proposed. The interaction among microgrids and the main grid is considered in the metrics. A multi-step performance assessment method for multi-microgrid systems is presented. Abstract: This paper proposes a set of new metrics for quantitatively assessing the performance of multi-microgrid systems which are operated in stand-alone mode. These metrics include generation penetration indices for indicating the configuration of distributed generations and loads, power exchange indices for representing energy interaction among microgrids and with the main grid, as well as reliability and economic indices for quantifying the reliable and economic operation of muti-microgrid systems. A multi-step performance assessment method for multi-microgrid systems is proposed, which considers different reliability requirements and economic characters of critical and non-critical loads as well as the energy exchange among microgrids and with the main grid for effectively calculating the proposed metrics. Case studies with practical data show the effectiveness of the proposed metrics and multi-step performance assessment method for assessing the performance of multi-microgrid systems.